Soft Robotics: Trends, Applications and Challenges Proceedings of the Soft Robotics Week, April 25-30, 2016, Livorno, Italy - Laschi, Cecilia; Rossiter, Jonathan; Iida, Fumiya; Cianchetti, Matteo; Margheri, Laura; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive, timely snapshot of current research, technologies and applications of soft robotics. The different chapters, written by international experts across multiple fields of soft robotics, cover innovative systems and technologies for soft robot legged locomotion, soft robot manipulation, underwater soft robotics, biomimetic soft robotic platforms, plant-inspired soft robots, flying soft robots, soft robotics in surgery, as well as methods for their modeling and control. Based on the results of the second edition of the Soft Robotics Week, held on April 25 - 30, 2016, in Livorno, Italy, the book reports on the major research lines and novel technologies presented and discussed during the event.
Introduction -- Soft bionics hands with a sense of touch through an electronic skin -- Soft robotics mechanosensing -- Towards Behavior Design of a 3D-printed Soft Robotic Hand -- Soft robotics in underwater legged locomotion: from octopus-inspired solutions to running robots -- Underwater soft robotics, the benefit of body-shape variations in aquatic propulsion -- Animal Models for Non-pneumatic Soft Robots -- Plant-inspired growing robots -- Bio-inspired soft aerial robots: adaptive morphology for high-performance flightflight -- Soft robots in surgery -- Design Principles for Soft-Rigid Hybrid Manipulators -- Eating, drinking, living, dying and decaying soft robots -- Soft-robot modelling, simulation and control in real-time -- Evolutionary Developmental Soft Robotics: towards adaptive and intelligent soft machines following nature's approach to design -- Morphosis - taking morphological computation to the next level. .
Keywords: Biomedical engineering; Control engineering; Robotics; Automation; Artificial intelligence; Computational intelligence; Biomedical Engineering and Bioengineering; Control, Robotics, Automation; Artificial Intelligence; Computational Intelligence